2018
DOI: 10.1016/s0140-6736(18)30473-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and undertreatment of mitral regurgitation: a community cohort study

Abstract: Mayo Clinic Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
179
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(192 citation statements)
references
References 42 publications
2
179
1
10
Order By: Relevance
“…In another study, Cortés and colleagues also did not find a link between MR improvement of 1 degree and 6-months mortality, however, reported-similar to our results-a trend towards increased cardiac mortality in patients with remaining MR ≥ 3 + at only 6-months of follow-up (24.4% vs. 15.7%; P = 0.151) [17]. Thus, MR improvement itself seems not to be necessarily related to better outcomes, but rather the absolute degree of MR following TAVR [19]. Two recent studies reported improved survival in patients with MR regression to none/mild MR following TAVR [18,20].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In another study, Cortés and colleagues also did not find a link between MR improvement of 1 degree and 6-months mortality, however, reported-similar to our results-a trend towards increased cardiac mortality in patients with remaining MR ≥ 3 + at only 6-months of follow-up (24.4% vs. 15.7%; P = 0.151) [17]. Thus, MR improvement itself seems not to be necessarily related to better outcomes, but rather the absolute degree of MR following TAVR [19]. Two recent studies reported improved survival in patients with MR regression to none/mild MR following TAVR [18,20].…”
Section: Discussionsupporting
confidence: 87%
“…Patient characteristics are presented in 19.5% mild to moderate MR), and 9.3% MR ≥ 3 + (6.6% moderate to severe MR, 2.7% severe MR; P < 0.001; Fig. 1).…”
Section: Patient Populationmentioning
confidence: 99%
“…At present, surgical treatment of isolated FMR remains uncommon because patients with FMR are often at high surgical risk due to LV dysfunction, older age and co‐morbidities . In addition, evidence on the prognostic benefit of MV surgery in patients with severe FMR who do not require CABG is limited and mostly restricted to patients with ischaemic FMR …”
Section: Functional Mitral Regurgitation: Everything We Need To Knowmentioning
confidence: 99%
“…However, prior studies estimated that nearly 30-50% of patients with severe VHD who met guideline criteria for intervention were not appropriately recognized or referred, [8][9][10][11] even in highly resourced environments. 7,12 There are an increasing number of treatment options available to patients with VHD; yet, not all patients are aware of or have access to the full spectrum of interventions. For most patients with severe primary MR, for example, it is well-recognized that mitral valve repair is superior to mitral valve replacement.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…It is now recognized that the longstanding effects of VHD can lead to irreversible changes in left ventricular (LV) function, repeated hospitalizations, patient morbidity (e.g., atrial fibrillation, heart failure, endocarditis), reduced quality of life (QOL), and premature mortality, which can often be prevented by earlier treatment. However, prior studies estimated that nearly 30–50% of patients with severe VHD who met guideline criteria for intervention were not appropriately recognized or referred, even in highly resourced environments …”
Section: Introductionmentioning
confidence: 99%